Instructional supervision and practices of teachers in physical exercise and sports programmes in public primary schools of Volta Region, Ghana - Donkor, Samuel Kofi; Domfeh, Charles; Hormenu, Thomas; Okala, Chikaike; Nkrumah, Abena Adasa; Osei, Charity Atteh; Agortey, Julius Jerry; Asare, Mavis; Adenyoh, Courage Kobla; Selase, Fortune Atsu; et al. (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2023)
Regular supervision of instructional tasks of the teacher is a powerful contributor to classroom achievement and effectiveness. The purpose of this study was to investigate instructional practices and frequency of supervision of teachers of PES programme in public primary schools and to explore gender differences in supervision of teachers in six educational circuits in the Volta Region, Ghana. We adopted a cross-sectional descriptive survey to investigate the pedagogical problems. We used 172 participants out of a population of 300 teachers in the study area. Good results based on the validity and reliability of the data collection instrument were achieved through expert consultation and the Cronbach alpha reliability test (ɑ ≥ .71). We conducted pre-data analyses to clean data from probable errors during data entering. Analyses of data using Statistical Package for Social Sciences (SPSS for Windows, Version 21) revealed that most teachers in public primary schools did not receive any form of supervisory assistance in teaching the PES programme in public primary schools. Findings showed that the PES programme was not taught regularly in public primary schools. Again, the findings revealed frequent cancellation of PES lessons and the use of PES time for other subjects such as English, Mathematics and Science in public primary schools. In terms of instructional supervision of the PES programme, both male and female teachers did not differ significantly. We recommended that the Ghana education service assign supervisory roles to qualified PES coordinators and resource persons to help teachers in public primary schools implement the PES curriculum successfully.